Design and Usability Evaluation of a Web-Based Car Service Monitoring System at FocusAuto - Darlene Syaroon Asalui; Benny Pinontoan; Mahardika Inra Takaendengan; Edwin Tenda; Stephano Caesar Wenston Ngangi; Dodisutarma Lapihu (Universitas Teknokrat Indonesia, 2026)
FocusAuto Repair Shop currently relies on manual WhatsApp updates for service status, resulting in delayed responses, inconsistent information, and limited transparency for customers. This condition reflects a broader challenge in information system adoption among Indonesian MSMEs. This study aims to design and implement a web-based car service monitoring system using the Rapid Application Development (RAD) method and evaluate its usability using the System Usability Scale (SUS). The system was developed through four RAD stages: Planning, Design, Construction, and Implementation, utilizing Laravel, Bootstrap, and MySQL. Key features include real-time status tracking, customer data management, and PDF invoice generation. System functionality was validated through Black-box testing involving 18 test scenarios for admin and customer modules. Usability was evaluated using the SUS questionnaire distributed to 10 FocusAuto customers. Results indicate that all 18 test scenarios passed successfully, confirming system reliability and functional compliance. The usability evaluation yielded an average SUS score of 85.25, categorizing the system as Excellent. These findings demonstrate that the developed system effectively replaces manual communication methods, significantly improving service transparency and operational efficiency at FocusAuto. The study concludes that web-based monitoring systems enhance customer satisfaction in automotive MSMEs. Future work recommends cloud deployment and WhatsApp API integration to further maximize accessibility and automation.